Optimalisasi UI/UX Aplikasi KRL Access: Studi Redesain Berbasis Design Thinking untuk Peningkatan Usability - Hanifah Murtafiatul Haq; Candra Milad Ridha Eislam; Muhammad Fikri Hilabi; Hanifah Murtafiatul HaqHanifah Murtafiatul Haq (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to improve the usability of the KRL Access application through a comprehensive redesign process grounded in the Design Thinking framework. The research employed a qualitative approach, focusing on user needs identified during interviews with active KRL commuters. Key issues regarding inefficient navigation, unclear icons, and limited visibility of essential features prompted the development of a streamlined interface with reorganized information hierarchy. A high-fidelity prototype was created to reflect these improvements, emphasizing clearer visual structure, reduced navigation depth, and faster access to scheduling information. Usability testing demonstrated notable improvements in user experience, particularly in task efficiency and perceived ease of use. Participants reported that the redesigned interface felt more modern, intuitive, and aligned with their expectations for rapid information retrieval. The findings indicate that incorporating user-centric design principles can significantly enhance the functionality and overall usability of public transportation applications. This research contributes practical insights into improving digital service platforms through iterative design and evaluation.